Costumed of scale inhibitors in oilfield water plant - León, Orietta; Cárdenas, Carmen; Carruyo, Jenny (Rev. Téc. Fac. Ing. Univ. Zulia)
The purpose of this work was to condition the chemical treatment, scale inhibitors, of a plant of dehydration of oilfield water. This water must fulfill the condition that the total hardness at the entry will be equal to the total hardness at the exit of the plant, to avoid the scale formation to cause: deferred Production, problems with the water injection, decrease in the heat transference, restriction in the flow (losses of pressure), corrosion by concentration cells, works of re-conditioning of wells due to production reduction, repairing and maintenance of the surface equipment, chemical additives consumption for cleanlining incrusted equipment. The analysis perfomed demonstrated that the water was scale forming. At the laboratory, several scale inhibitors was evaluated. The scale inhibitors were divided for its study according to its active matter in: polyacrilates, fosfonates, polyfosfonates and a mixture of fosfonates and polyacrilates The scale inhibitors based on polyacrilate, polyfosfonate and a mixture of polyacrilate-fosfonate, obtained a 100% of efficiency in the laboratory for diff rent concentrations.